Sulfide Passivation of Indium Phosphide Porous Surfaces - Y.O. Suchikova (Журнал нано- та електронної фізики)
The paper describes the effect of the chemical treatment of porous indium phosphide in sulfide solutions on the photoluminescence spectrum. It was shown that the surface sulfiding samples leads to a state of inertia with respect to oxygen. It is found that the thin crystal film is formed of a chemically inert material during chalcogenide passivation por-InP removes oxide layer instead.